Changes in Provider Type and Prescription Refills Among Privately Insured Children and Youth With ADHD - Hart, Laura C. (J Atten Disord, 2020)
OBJECTIVE: The aim of this paper is to understand associations between age and health care provider type in medication continuation among transition-aged youth with ADHD. METHOD: Using an employer-sponsored insurance claims database, we identified patients with likely ADHD and receipt of ADHD medications. Among patients who had an outpatient physician visit at baseline and maintained enrollment at follow-up 3 years later, we evaluated which ones continued to fill prescriptions for ADHD medications. RESULTS: Patients who were younger at follow-up more frequently continued medication (77% of 11–12 year-olds vs. 52% of 19–20 year-olds). Those who saw a pediatric provider at baseline and follow-up more frequently continued to fill ADHD medication prescriptions than those who saw a pediatric provider at baseline and non-pediatric providers at follow-up (71% vs. 53% among those ages 15–16 years at follow-up). CONCLUSION: Adolescents and young adults with ADHD who changed from pediatric to exclusively non-pediatric providers less frequently continued to receive ADHD medications.